The protein phosphatase with EF‐hand domain 1 is a calmodulin‐binding protein that interacts with proteins involved in sperm capacitation, binding to the zona pellucida, and motility. Issue 4 (30th March 2021) - Lavoie‐Ouellet, Camille; Clark, Marie‐Ève; Ruiz, Juliana; Saindon, Andrée‐Anne; Leclerc, Pierre
Abstract: Spermatozoa are highly specialized cells whose fertilizing and motility functions highly depend on intracellular Ca 2+ ‐mediated events and protein posttranslational modifications like phosphorylation. Our group previously identified PPEF1, the Ser/Thr phosphatase with EF‐hand domain 1, among calmodulin‐affinity pulled down sperm proteins. As the mammalian ortholog of the Drosophila phosphatase rdgC that dephosphorylates rhodopsin, PPEF1 has been studied mostly in the retina. The presence and importance of this Ca 2+ /calmodulin‐binding protein phosphatase has not been studied in sperm or testicular functions despite its high expression level. In this study, we show that PPEF1 is present in testicular germ cells, and in mouse, human and bull spermatozoa where it is localized predominantly in the neck and acrosome areas. Different transcript variants encoding four predicted isoforms were detected by reverse transcription polymerase chain reaction in bull testis, spermatocytes and spermatids. Phosphatase activity of immunoprecipitated sperm PPEF1 was detected using the substrate pNPP and analysis of the coimmunoprecipitated proteins reveal an enrichment in the biological processes of sperm capacitation, binding to the zona pellucida and motility. Although this is the first demonstration of the presence of PPEF1 in sperm and testicular germ cells, its involvement in sperm fertilizing ability and motility, and the mechanisms regulating its activity remain to be further investigated.